POTENTIAL OF LOSS OF ORGANIC FERTILIZER IN LOWLAND RICE FARMING IN KLUNGKUNG DISTRICT, BALI - I Nengah Muliarta; Jhon Hardy Purba (Agro Bali : Agricultural Journal, 2020)
Rice straw is an abundant resource that was still seen as a waste in intensive rice cultivation. Rice straw is said to be a resource because it can be used as organic fertilizer (compost) and contains nutrients that were beneficial for crop growth and soil fertility. The fact in the field was still found that rice straw was wasted, one of which was burned. A study was conducted through a method of observation and survey involving rice paddy farmers in 3 sub-districts in the district of Klungkung, namely Banjarangkan, Klungkung and Dawan. The aim of the research was to know the production of rice straw waste and the potential of wasted organic fertilizer in intensive rice cultivation. Based on the results obtained the production of dried straw waste in each harvest about 10.21 tons/ha.  Farmers do not utilize rice straw as compost by reason, not knowing how to composting. There were 30.34% of farmers who burn straw because based on the knowledge gained burn is an easy way to restore rice straw to the ground. The impact of burning rice straw was around 5,887,086 - 7,888.7 tons of organic fertilizer wasted.